N‐Alkylated Analogues of Indolylthio Glycosides as Glycosyl Donors with Enhanced Activation Profile. Issue 18 (12th May 2022) - Shrestha, Ganesh; Panza, Matteo; Singh, Yashapal; Stine, Keith J.; Demchenko, Alexei V.
Abstract: While studying indolylthio glycosides, previously we determined their activation profile that required large excess of activators. This drawback was partially addressed in the present study of N‐alkylated SInR derivatives. The activation process was studied by NMR and the increased understanding of the mechanism led to a discovery of different activation pathways taking place with SIn versus SInR derivatives. Also investigated was orthogonality of the SInR leaving groups versus thioglycosides and selective activation of thioimidates over SInR glycosides. Abstract : Protecting the nitrogen atom in the S‐indolyl leaving group of glycosyl donors helped to reduce the amount of NIS/TfOH required for their activation in glycosylation. The activation with silver salts shifted from the remote to the direct activation pathway offering additional insight into the reaction mechanism by which these leaving groups are activated.